2017
DOI: 10.1002/ece3.3065
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating hybridization capture with RAD probes as a tool for museum genomics with historical bird specimens

Abstract: Laboratory techniques for high‐throughput sequencing have enhanced our ability to generate DNA sequence data from millions of natural history specimens collected prior to the molecular era, but remain poorly tested at shallower evolutionary time scales. Hybridization capture using restriction site‐associated DNA probes (hyRAD) is a recently developed method for population genomics with museum specimens. The hyRAD method employs fragments produced in a restriction site‐associated double digestion as the basis f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 57 publications
2
34
0
Order By: Relevance
“…In this study, we took advantage of the availability of museum specimens from different locations and time points to provide an insight into the genetic dynamics of O. decorus at both spatial and temporal scales. By successfully applying hyRAD to 119 specimens, we retrieved more than a thousand of SNPs, a major improvement compared to previous studies using museum specimens (e.g., Kindler et al., ; Spurgin et al., ), confirming the recent findings of Linck, Hanna, Sellas, and Dumbacher (), who successfully tested hyRAD on bird samples.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In this study, we took advantage of the availability of museum specimens from different locations and time points to provide an insight into the genetic dynamics of O. decorus at both spatial and temporal scales. By successfully applying hyRAD to 119 specimens, we retrieved more than a thousand of SNPs, a major improvement compared to previous studies using museum specimens (e.g., Kindler et al., ; Spurgin et al., ), confirming the recent findings of Linck, Hanna, Sellas, and Dumbacher (), who successfully tested hyRAD on bird samples.…”
Section: Discussionsupporting
confidence: 83%
“…By successfully applying hyRAD to 119 specimens, we retrieved more than a thousand of SNPs, a major improvement compared to previous studies using museum specimens (e.g., Kindler et al, 2012;Spurgin et al, 2014), confirming the recent findings of Linck, Hanna, Sellas, and Dumbacher (2017), who successfully tested hyRAD on bird samples.…”
Section: Application Of Hyrad: Future Prospects and Challenges In Msupporting
confidence: 78%
“…There are several methods for accounting for post-mortem damage in specimens. Generally these techniques fall into two categories: (a) Presequencing repair and high-fidelity polymerase enzymes that increase amplification efficiency (Bi et al, 2013;Binladen et al, 2006;Burrell et al, 2015;Rowe et al, 2011;Willerslev & Cooper, 2005), and (b) post-sequencing filtering and weighting of damaged regions (Bi et al, 2013;Jónsson, Ginolhac, Schubert, Johnson, & Orlando, 2013;Linck, Hanna, Sellas, & Dumbacher, 2017;Zhou et al, 2017).…”
Section: Dna Repair Kitsmentioning
confidence: 99%
“…There has been increasing effort to develop reduced-representation sequencing methods that maximize the data generated from historical samples (e.g., Besnard et al, 2016;Bi et al, 2013;Burrell et al, 2015;Lim & Braun, 2016;Linck et al, 2017;McCormack et al, 2016;Suchan et al, 2016). Generally, these reduced-representation sequencing approaches are best suited to hDNA because they sequence smaller fragments of DNA (Bi et al, 2013;Hung et al, 2013;McCormack et al, 2016;Suchan et al, 2016).…”
Section: Whole Genome and Reduced-representation Sequencing For Hdnamentioning
confidence: 99%
“…For example, by comparing historical (2000)(2001)(2002) and recent (2010-2012) genetic data, Taylor et al (2014) showed that the hybrid zone between Black-capped Chickadee (Poecile atricapillus) and Carolina Chickadee (P. carolensis) in Pennsylvania has moved north due to changing winter temperatures. However, a temporal comparison is only possible when historical data is available or can be obtained from museum specimens (Spurgin et al 2014;Linck et al 2017). An alternative strategy is to compare different hybrid zones between the same species (Schaefer et al 2016;Kingston et al 2017;Lackey and Boughman 2017).…”
Section: Genomic Clines In Hybrid Zonesmentioning
confidence: 99%